Software Model for Determining the Optimal Routes in a Computer Network Based on the Two-Colonial Ant Algorithm - Pakhomova, V. M; Opriatnyi, A. O (Nauka ta progres transportu, 2021)
Purpose. At present, the computer networks of the information and telecommunication system (ITS) of railway transport use the OSPF protocol, which does not allow taking into account several metrics when determining the optimal route. Therefore, there is a need to study the possibility of organizing routing in computer networks of rail transport ITS using a two-colonial ant algorithm. Methodology. According to the Two-ACO software model, created in the Python language based on the two-colonial ant algorithm, the optimal route in a computer network was determined. Two-ACO model inputs: computer network parameters (network adjacency matrix, number of routers); parameters of the ant algorithm (number of iterations; number of ants in the colony; number of elite ants; initial pheromone level; evaporation rate; parameter for adjusting the amount of pheromone deposition). Findings. The results of the Two-ACO model are presented in the form of graphs depicting the optimal paths: the criterion of the total delay on the routers (for the first colony of ants) and the number of hops (for the second colony of ants). Originality. According to the created Two-ACO software model for a computer network of 7 routers and 17 channels, a study of the time for determining the optimal path in a computer network by the number of ordinary and elite ants, evaporation rate and deposited pheromone was conducted. It is determined that it is enough to use the number of ants equal to the number of routers and have 2 elite ants in the colony, with 1000 iterations, evaporation rate from 0.2 to 0.7, and pheromone deposition by ants close to one. Practical value. Created Two-ACO software model using two colonies of ants on the following criteria: the total delay on the routers (for the first colony of ants) and the number of hops that make up the route (for the second colony of ants) allows you to parallel determine the optimal routes in a computer network of railway transport. It is estimated that for a computer network of 15 routers and 17 channels, it is sufficient to have 30 agents (two ants on top), the value of the pheromone deposited by the agents is close to one, and the evaporation rate is 0.4. Мета. На сучасному етапі в комп’ютерних мережах інформаційно-телекомунікаційної системи (ІТС) залізничного транспорту використовують протокол OSPF, який не дозволяє враховувати декілька метрик під час визначення оптимального маршруту. Тому ми ставимо за мету дослідити можливість організації маршрутизації в комп’ютерних мережах ІТС залізничного транспорту за допомогою двоколоніального мурашиного алгоритму. Методика. За програмною моделлю «Two–ACO», створеною мовою Python за двоколоніальним мурашиним алгоритмом, визначено оптимальний маршрут у комп’ютерній мережі. Вхідні дані моделі «Two–ACO»: параметри комп’ютерної мережі (матриця суміжності мережі, кількість маршрутизаторів); параметри мурашиного алгоритму (кількість ітерацій; кількість мурах у колонії; кількість елітних мурах; початковий рівень феромону; коефіцієнт випаровування; параметр для регулювання величини відкладеного феромону). Результати. Визначення за програмною моделлю «Two-ACO» оптимального маршруту подано у вигляді графів із зображенням на них оптимальних шляхів: за критерієм сумарної затримки на маршрутизаторах (для першої колонії мурах) та кількістю хопів (для другої колонії мурах). Наукова новизна. За створеною програмною моделлю «Two–ACO» для комп’ютерної мережі із 7 маршрутизаторів та 17 каналів проведено дослідження часу визначення оптимального шляху за кількістю звичайних та елітних мурах, значеннями коефіцієнта випаровування та відкладеного феромону. Установлено, що достатньо використовувати кількість мурах, що дорівнює кількості маршрутизаторів, мати в колонії 2 елітних мурах, при цьому вистачає 1 000 ітерацій, коефіцієнта випаровування від 0,2 до 0,7, а відкладеного феромону мурахами близького до одиниці. Практична значимість. Створена програмна модель «Two–ACO» з використанням двох колоній мурах за загальною затримкою на маршрутизаторах та кількістю хопів, що складають маршрут, дозволяє паралельно визначити оптимальні маршрути в комп’ютерній мережі залізничного транспорту. З’ясовано, що для комп’ютерної мережі з 15 маршрутизаторів та 17 каналів достатньо мати 30 агентів (двох мурах на вершину), значення феромону, відкладеного агентами, близьке до одиниці, при цьому коефіцієнт випаровування складає 0,4.